PERAN KEPALA KELURAHAN DALAM UPAYA MENCEGAH TERJADINYA KRIMINALITAS DI KELURAHAN BITUNG KARANGRIA KECAMARAN TUMINTING KOTA MANADO - Bangsuil, Satria Junianto (HOLISTIK, Journal Of Social and Culture, 2014)
Crime is one of the problems that there is always in human life. Almost no one area of the community was that regardless of the problem of criminality, both in the area of limited community, and the broad community. Problems alsooften become the area, for the sake of crime problems where the children who dropped out of the school is to slip away with criminal caused a number of factors as with liquor, free sex, and the economy of the family.TORANG SAMUABASUDARA. The term is now been not become a tool adhesive among residents but that becomes more important is about the interests of certain parties like thugs. Thing to be regrettable is recognition for orderly social been abandoned by particular persons as a result of the interests of a moment. Players evencrimes involving children the teenager and youth even they still while schools.Manage serious criminality that already goods will certainly require handling hence sub-district government considered importantand decisive in preventing and remedying the occurrence of the problem of criminality.The urban village is not only the duty of government,as in the development of and tasks but also hold by the government to thepublic, especially in urban villages and community development in order tocarry out.Keywords: crime, problem, government